Exploring the dimensions of image management using interpretive structural modelling and MICMAC analysis. (2016) - Uppaal, Kuiljeit; Singh, Manju
The buzz word today is image management. It has had people intrigued and curious, and yet unaware of its concept as well as what it envelopes. In the academic world, it is a relatively untouched area as a complete concept, which thereby urges the need for study and makes it highly pertinent for research. The concept of image management which spans an entirety of elements that comprise it also offers a way out for growth and enhancement for us human beings, our need for acceptance, growth and recognition, as well as aspirations in the dynamism of the contemporary world at a personal as well as professional level. The research paper throws light on the brief history and evolution of image management and an understanding of the concept of image management. It also highlights the core elements of image management which have been arrived at based on systematic literature review as well as interpretive structural modelling (ISM) approach and MICMAC analysis; coupled with the interrelationship between the varied elements of the concept of image management.